2022
DOI: 10.3390/antibiotics11020196
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Dissemination Capacities of a blaNDM-5-Harboring IncX-3 Plasmid in Escherichia coli Isolated from an Urban River in Montpellier, France

Abstract: To investigate the capacities of persistence and dissemination of blaNDM-5 within Escherichia coli and in aquatic environment, we characterized E. coli (sequence type 636) strains B26 and B28 isolated one month apart from the same urban river in Montpellier, France. The two isolates carried a pTsB26 plasmid, which sized 45,495 Kb, harbored blaNDM-5 gene and belonged to IncX-3 incompatibility group. pTsB26 was conjugative in vitro at high frequency, it was highly stable after 400 generations and it exerted no f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 92 publications
1
8
0
Order By: Relevance
“…39.9% of the complete plasmids (n = 218) predicted to harbor oriT site, MOB and MPF simultaneously, which can be classified as conjugative. Although the typical oriT site were not predicted on the IncX3 plasmids (n = 179, 32.8%), its high conjugation transfer frequency has been confirmed in previous studies [18,19]. 30 different Inc-MOB-MPF combinations were observed and the top 3 combinations in quantity were highlighted and displayed with date in Supplementary Fig.…”
Section: Bla Ndm -Harboring Plasmids Showed Extensive Modularity and ...supporting
confidence: 57%
See 1 more Smart Citation
“…39.9% of the complete plasmids (n = 218) predicted to harbor oriT site, MOB and MPF simultaneously, which can be classified as conjugative. Although the typical oriT site were not predicted on the IncX3 plasmids (n = 179, 32.8%), its high conjugation transfer frequency has been confirmed in previous studies [18,19]. 30 different Inc-MOB-MPF combinations were observed and the top 3 combinations in quantity were highlighted and displayed with date in Supplementary Fig.…”
Section: Bla Ndm -Harboring Plasmids Showed Extensive Modularity and ...supporting
confidence: 57%
“…Here, we further explored the geographical dominance, host source specificity, bacterial genera, and dominant Inc type of plasmid for a better understanding of complex transfer modes of specific gene background. According to the observations of currently available data, IncX3 plasmid occupied a large fraction of the dominant cluster, and was identified in diverse geographical locations, host sources, and bacterial genera suggesting the wide spread and low fitness cost of IncX3 plasmid, as previous reported [7,18,19,33,34]. We hypothesized that IncX3 could be the dominant bla NDM -harboring plasmids in the next a few years.…”
Section: Discussionmentioning
confidence: 66%
“… K. pneumoniae genomes used were retrieved from the K. pneumoniae database ( https://bigsdb.pasteur.fr/klebsiella/ ). The genetic context of bla OXA-48 , bla OXA-181 , and bla DHA-1 and linear plasmid comparisons were generated and visualized using EasyFig v2.2.2 ( 43 ). Phylogeny of IncL plasmid from this study and 10 others retrieved from the NCBI database (last accessed February 2022) was generated with megaX v0.1 ( 44 ).…”
Section: Methodsmentioning
confidence: 99%
“…The ndm /IncX3 plasmid is thought to confer a low fitness cost that contributes to its worldwide occurrence [ 10 , 11 ]. However, some studies have also reported high fitness costs [ 12 , 13 ], though the variety of fitness costs and the mechanism involved remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This cost in fitness has been attributed to plasmid properties, such as the number of copies, size of the plasmid, and related metabolic burden [ 4 , 5 , 6 , 7 ]. The ndm /IncX3 plasmid was considered to confer a low fitness cost because of its low copy number, minor metabolic burden, and stable genetic backbone [ 8 , 9 , 10 , 11 ]; however, high fitness costs have been reported in some E. coli strains [ 12 , 13 ]. The mechanism of the diversity of fitness costs while carrying the ndm /IncX3 plasmid remains unclear and is potentially unrelated to the general properties of the plasmid.…”
Section: Introductionmentioning
confidence: 99%